2019
DOI: 10.1093/ofid/ofz024
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Predisposing Factors of John Cunningham Virus-Induced Progressive Multifocal Leukoencephalopathy in Southern Finland: A Population-Based Study

Abstract: Background The aim of this study was to assess the prevalence, incidence rate (IR), predisposing factors, survival rate, and diagnostic delay of progressive multifocal leukoencephalopathy (PML) across medical specialties. Another objective was to survey how PML diagnosis was made in the studied cases. Methods This is a cross-sectional retrospective observational study of PML cases across different medical specialties during 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…Finnish population-based registry study investigating the period 2004–2014 reported an overall lower PML incidence of 0.072/100,000 person-years with no temporal incidence trend despite the increasing use of mAbs at the national level 27. In the most recent study from southern Finland in 2004–2016, we reported a PML-incidence of 0.12/100,000 person-years with no sign of increase 28. In this study the data was obtained from clinical records and the HIV Quality Registry.…”
Section: Epidemiology Of Pmlmentioning
confidence: 50%
See 2 more Smart Citations
“…Finnish population-based registry study investigating the period 2004–2014 reported an overall lower PML incidence of 0.072/100,000 person-years with no temporal incidence trend despite the increasing use of mAbs at the national level 27. In the most recent study from southern Finland in 2004–2016, we reported a PML-incidence of 0.12/100,000 person-years with no sign of increase 28. In this study the data was obtained from clinical records and the HIV Quality Registry.…”
Section: Epidemiology Of Pmlmentioning
confidence: 50%
“…Increased use of mAbs and HSCT correlate with rising PML incidence among patients with hematologic malignancies 30. Hematologic conditions associated with PML include CLL, Hodgkin’s disease, non-Hodgkin’s lymphoma, acute myeloid leukemia, acute lymphoblastic leukemia, Waldeström macroglobulinemia, multiple myeloma, polycythemia vera, and mycosis fungoides 28,29,31. Major PML risk factors are uncontrolled Hodgkin’s disease, treatment with purine analogues, and treatments related to HSCT 32.…”
Section: Epidemiology Of Pmlmentioning
confidence: 99%
See 1 more Smart Citation
“…While the fatality rate of PML has been significantly reduced by restoration of immune function and most PML patients now survive, most experience significant morbidity [42][43][44][45]. HIV-associated PML still remains one of the most common types of PML, but no longer accounts for the overwhelming majority of new cases due to the availability of HAART and the emergence of new risk factors for PML [46,47]. Though it is one of the only treatments available for PML, restoration of immune function needs be carefully managed because it can lead to a fatal inflammatory reaction called immune reconstitution inflammatory syndrome or IRIS [48][49][50].…”
Section: Progressive Multifocal Leukoencephalopathy (Pml)mentioning
confidence: 99%
“…As such, other classifications of PML are exceedingly rare [58,59]. The prevalence of PML worldwide is often estimated to be about two cases per 100,000 individuals, though this number varies by population [47,60].…”
Section: Drug-induced Pmlmentioning
confidence: 99%